Bacterial community structure and predicted function in an acidogenic sulfate-reducing reactor: Effect of organic carbon to sulfate ratios. (December 2019) - Li, Jun; Cai, Min-Hui; Miao, Yu; Luo, Gan; Li, Wen-Tao; Li, Yan; Li, Ai-Min
Graphical abstract: Highlights: Acidogenic sulfate-reducing reactor was used for high influent sulfate content. Microbial community structure and bacterial connections network were analyzed. Desulfovibrio was the most predominant SRB in acidogenic sulfate-reducing reactor. Sulfate reduction functional genes and pathway were predicted by PICRUSt. Abstract: A lab-scale acidogenic sulfate-reducing reactor with N2 stripping was continuously operated to uncover its microbial mechanism treating highly sulfate-containing organic wastewaters. Results showed that sulfate reduction efficiency decreased with the influent COD/sulfate ratios. Microbial community analysis showed that VFA accumulation mainly caused by the predominance of fermentative bacteria including Streptococcus and Oceanotoga . Genus Desulfovibrio was the most predominant SRB and enriched at low influent COD/sulfate ratios. Although Bifidobacterium, Atopobium, Wohlfahrtiimonas, Dysgonomonas etc. had low average abundance, they were identified keystone genera by the co-occurrence network analysis. The functions of the microbial community were not insignificantly influenced by COD/sulfate ratios. All predicted functional genes involved in dissimilatory sulfate reduction reached their maximum abundances at influent COD/sulfate ratio of 1.5, while the assimilatory sulfate reduction was favored at the COD/sulfate ratio lower than 2.